Effect of Macroporous Chitosan-Tripolyphosphate Beads on COD and Turbidity Values in Sasirangan Wastewater - Ariyani, Dahlena; Maulana, Riana; Irawati, Utami; Mujiyanti, Dwi Rasy; Umaningrum, Dewi (Universitas Diponegoro, 2026)
A batch system was applied to study the effect of using macroporous cross-linked chitosan–tripolyphosphate (TPP) beads on chemical oxygen demand (COD) values and turbidity in Sasirangan wastewater. The ionic cross-linking reagent, sodium tripolyphosphate, was used to obtain more rigid chitosan beads, and sodium bicarbonate was added as a porogen. COD values were analyzed using the titrimetric method, and turbidity values were analyzed using the turbidimetric method. This analysis was used to study the effect of dose and pH on the performance of beads in Sasirangan wastewater. Scanning electron microscopy (SEM) characterization of the beads showed that NaHCO₃ as a porogen enlarged the pores in the chitosan–TPP beads, and Fourier-transform infrared (FTIR) characterization showed interactions among chitosan, chitosan–TPP beads, and wastewater. The results showed that higher chitosan dosages resulted in increased final COD values in Sasirangan wastewater, and the higher the pH, the higher the COD value. The addition of beads reduced the turbidity value of the Sasirangan wastewater, with higher doses leading to greater turbidity reduction, with the optimum achieved at 400 mL/L. The pH conditions did not affect the reduction in the turbidity value, with less than 1% variation observed.